Пурандық ведалық трактаттар контексіндегі адамның өзін-өзі сәйкестендіруінің рухани аспектілер - A., Zholomanova; B., Karipbaev (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2021)
Spiritual comprehension of one’s own place in this world, awareness of oneself, one’s own mission by the human community and an individual human unit in particular, is of everlasting importance. Since the presence of self-identification is a kind of acquisition of the frame of the personality, the value guideline, the personality should first of all find answers to these questions and only then live in this world. But the rapid course of daily events, the existence in the plane of consumer values, constantly changing events does not allow a person to acquire a conscious state in the development of this issue. The article aims to expand the boundaries of self-awareness as a person through the ancient Indian knowledge of man, his spiritual component, in terms of the ancient Puranas, Srimad-Bhagavatam – the quintessence of Vedic knowledge. The study of the topic of self-identification of the human person in the spiritual aspect through the prism of ancient Eastern philosophical sources, since the truth should be sought in antiquity, contains the scientific significance of the work. It is obvious that the research and inventions of subsequent generations of philosophers formed the state of the worldview crisis of modern society. Any stable worldview presupposes the presence of a clear position on the issue of a person’s self-identification; accordingly, the root of the problems should be sought in who the person believes himself to be. The Puranic scriptures consider the answer to this question to be meaningful, since depending on this, a life paradigm, a worldview perspective will be built. The value of this study consists in studying the topic of self-identification, which is manifested in the modern world extremely vaguely or not at all studied, which gives rise to spiritual, personal and ideological crises. The special value of the work in the application of ancient oriental sacred texts for solving modern problems, this testifies to the practicality of the ancient texts of the ancient civilization of Bharata-Varsha. The study of Puranic texts will allow us to correlate modern paradigms of the worldview with other points of view and take into account the importance of the spiritual platform of human nature, which means awareness of oneself as a soul. Key words: self-identification, spirituality, Vedas, ancient Indian philosophy, worldview.